Red China Prisoner: My Years Behind Bamboo Bars - Sara Perkins 1892- (UK Pickering & Inglis, 1963)
The autobiography of the American missionary who was held captive in Communist China for four and a half years.
Keywords: Spiritual Theology (3GddGghJ GdQhMjs; Theology -- Correspondence; Missionaries; Missionaries -- China -- Biography; Missions -- China; Presbyterian Church -- Missions